POLA PENINGKATAN KUALITAS PEMBELAJARAN LINGKUNGAN HIDUP SISWA KELAS XI IA SMA NEGERI 9 SEMARANG PADA POKOK BAHASAN PENCEMARAN LINGKUNGAN MELALUI PENDEKATAN KONTEKSTUAL BERWAWASAN SETS 1 - Sudarman, - (Universitas Negeri Semarang, 2007)
The aim of this learning research with approach contextual with vision of thisSETS is to improve the environmental learning quality with indicators: enthusiastic,result of ledming and classical completed. The conclusion of this research areenthusiastic result of learning and classical completed improved. Cycle 1: 33,33%student is very enthusiastic, the average of learning result is 74,56, the classicalcompleted is 86,67%. Cycle 2: 40,48% student is very enthusiastic, the average oflearning result is 76,23, the classical cOJI,lpleted is 91,11 %. Cycle 3: 53,38% studentis very enthusiastic, the average of learning result is 77,56, the classical completed is95,56%Keyword: kontekstual, SETS, peningkatan, kualitas, pembelajaran lingkungan hidup